A self-paced-reading study on the effects of structured input and textual enhancement on the acquisition of the Italian subjunctive of doubt. Issue 2 (16th October 2020) - Chiuchiù, Gaia; Benati, Alessandro
Abstract : The present study investigates the effects of structured input and textual enhancement on the acquisition of the Italian subjunctive of doubt using a self-paced reading test. The main questions of this study are: (1) Would L2 learners exposed to structured input and textual enhancement demonstrate sensitivity to violations of the Italian subjunctive of doubt as measured by a self-paced reading test? (2) Would L2 learners exposed to structured input and textual enhancement demonstrate the ability to comprehend sentences containing the subjunctive of doubt? Eighteen Chinese (L1) subjects learning Italian in a private school were randomly assigned to two instructional groups: structured input (n = 9); and textual enhancement (n = 9). Neither instructional treatments included explicit information. The main results from the self-paced reading task indicated that only the structured input group showed higher sensitivity to violations, and this group improved from pre-test to post-test in the ability to comprehend sentences containing the target feature under investigation.